Risk factors of enteral feeding intolerance in severe acute pancreatitis patients: A protocol for systematic review and meta-analysis. Issue 18 (7th May 2021) - Fan, Hongyun; Yang, Chunchun; Duan, Zhiying; Huo, Xiaohui; Yang, Yang
Abstract: Background: Patients with severe acute pancreatitis (SAP) have gastrointestinal dysfunction, and enteral nutrition intolerance is easy to occur during the implementation of enteral nutrition, which leads to the suspension or termination of enteral nutrition. Enteral nutrition cannot tolerate the influence of many factors. At present, there is a lack of analysis on the influencing factors of enteral nutrition intolerance in patients with SAP. Therefore, this study analyzed the factors of enteral nutrition intolerance in patients with SAP by meta-analysis, to provide a basis for the protection of enteral nutrition in patients with SAP. Methods: Databases (PubMed, Embase, Cochrane Library, Web of Science, China Biology Medicine Database, China National Knowledge Infrastructure, China Science and Technology Journal Database, and Wanfang) were searched using index words to find relevant studies published before March 2021. Meta-analyses of relative risk were performed for the identification of risk factors. Results: We will disseminate the findings of this systematic review and meta-analysis via publications in peer-reviewed journals. Conclusion: This study systematically reviewed the existing evidence and determined the incidence and predictors of enteral nutrition intolerance in patients with SAP.